2016
DOI: 10.3390/ijms17060857
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hedgehog Signaling Pathway in NASH

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the number one cause of chronic liver disease in the Western world. Although only a minority of patients will ultimately develop end-stage liver disease, it is not yet possible to efficiently predict who will progress and, most importantly, effective treatments are still unavailable. Better understanding of the pathophysiology of this disease is necessary to improve the clinical management of NAFLD patients. Epidemiological data indicate that NAFLD prognosis is dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 85 publications
3
28
0
Order By: Relevance
“…These results are consistent with the finding of a previous study indicating that individuals with a mutated Smo gene were resistant to the progress of NAFLD (17). It is noteworthy that the exposure of normal hepatocytes with saturated fatty acids and lysophospholipids results in an increased expression of HH signaling pathway ligands (11). Therefore, there is a little chance that the expression of HH ligand in individuals with steatosis would be reduced due to exposure to lipid accumulation.…”
Section: Hedgehog Signaling Pathwaysupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with the finding of a previous study indicating that individuals with a mutated Smo gene were resistant to the progress of NAFLD (17). It is noteworthy that the exposure of normal hepatocytes with saturated fatty acids and lysophospholipids results in an increased expression of HH signaling pathway ligands (11). Therefore, there is a little chance that the expression of HH ligand in individuals with steatosis would be reduced due to exposure to lipid accumulation.…”
Section: Hedgehog Signaling Pathwaysupporting
confidence: 92%
“…These hepatocytes are important sources of HH ligands (10) since the high amounts of HH pathway ligands is observed in human and animal NASH specimens. In addition, there is a direct relationship between the severity of liver disease and the activity of the HH pathway in the NAFLD from the NASH phase (11). Further investigations indicated that the expression of HH ligands in the liver tissue of patients with NASH cirrhosis was significantly higher than their expression in the liver tissue with SS (9).…”
Section: Hedgehog Signaling Pathwaymentioning
confidence: 96%
See 1 more Smart Citation
“…There is increasing evidence supporting a role for dysregulation of the hedgehog (Hh) pathway in the pathogenesis of both adult and pediatric NAFLD . Hh, a morphogenic signaling pathway, controls organogenesis during organ development and is usually quiescent in adolescents and adults.…”
mentioning
confidence: 99%
“…Although typically silent, Hh may be reactivated during injury that stimulates Hh ligand production. In the liver injury incited in both adult and pediatric NAFLD, activation of the Hh pathway is a dominant mechanism by which fibro‐inflammatory repair occurs …”
mentioning
confidence: 99%